Homo- and copolymerization of phenacyl methacrylate via the atom transfer radical polymerization method - Coskun, M. Fatih; Demirelli, Kadir; Coskun, Mehmet (Taylor & Francis Inc, 2007)
The homo- and copolymers via atom transfer radical (co)polymerization (ATRP) of phenacyl methacrylate (PAMA) with methyl methacrylate (MMA) and t-butyl methacrylate (t-BMA) was performed in bulk at 90 degrees C in the presence of ethyl 2-bromoacetate, cuprous(I)bromide (CuBr), and 2,2'-bipyridine. The polymerization of PAMA was carried out at 70, 80, and 100 degrees C. Also, free-radical polymerization of PAMA was carried out at 60 degrees C. Characterization using FT-IR and C-13-NMR techniques confirmed the formation of a five-membered lactone ring through ATRP. The in situ addition of methylmethacrylate to a macroinitiator of poly(phenacyl methacrylate) [Mn = 2800, Mw/Mn = 1.16] afforded an AB-type block copolymer [Mn = 13600, Mw/Mn = 1.46]. When PAMA units increased in the living copolymer system, the Mn values and the polydispersities were decreased (1.1 < Mw/Mn < 1.79). The monomer reactivity ratios were computed using Kelen-Tudos (K-T), Fineman-Ross (F-R) and Tidwell-Mortimer (T-M) methods and were found to be r(1) = 1.17; r(2) = 0.76,- r(1) = 1.16; r(2) = 0.75 and r(1) = 1.18; r(2) = 0.76, respectively (r(1) = is monomer reactivity ratio of PAMA). The initial decomposition temperatures of the resulting copolymers were measured by TGA. Blends of poly(PAMA) and poly(MMA) obtained via the ATRP method have been characterized by differential thermal and thermogravimetric analyses.
Keywords: ATRP; blend; thermal analysis; monomer reactivity ratio; lactone end